ASUPAN GIZI DAN POLA MAKAN ANAK STUNTING USIA 12-23 BULAN DI DESA LOKASI KHUSUS (LOKUS) KABUPATEN CIREBON - Dwi Kusumayanti Dwi Kusumayanti; Dewi Marhaeni Dewi M Diah Herawati (PERSATUAN AHLI GIZI INDONESIA, 2021)
Stunting is a health problem in Cirebon Regency, 24.9 percent of er two years old are stunted. The problem of stunting that occurs during the age period of er two years old is the lack of nutrient intake which is influenced by the mother's upbringing in feeding her child. The purpose of this study was to determine the nutritional intake and diet of stunting children aged 12-23 months in the locus village of Cirebon Regency. The design is a mixed-method with a sequential explanatory strategy. Quantitative research to see the food intake of stunting children while qualitative research was used to determine the diet of stunting. Quantitative samples were 40 people, carried out in total sampling, while qualitative as many as 10 people were done by purposive sampling. Quantitative data collection is done through child height measurements and multiple 24-hour recalls for 3 days. Qualitative data collection is done by in-depth interviews. Quantitative data analysis was carried out descriptively, while qualitative data analysis was carried out through transcription, coding, categorization, theme making. The results showed that the nutritional intake of stunting children aged 12-23 months in the locus village of Cirebon Regency was 80% AKG (inadequate) for energy, protein, vitamin A, vitamin C, calcium, and zinc. The dietary pattern of stunting children aged 12-23 months in the locus village of Cirebon Regency is a non-varied menu, the frequency of inappropriate feeding, the number of less, types that are not diverse and irregular schedules than recommended. Nutritional intake does not meet the needs of children, while the dietary pattern is not following the standards of the Ministry of Health.Keywords: nutritional intake, dietary pattern, stunting children, ages 12-23 months ABSTRAK Stunting menjadi masalah kesehatan di Kabupaten Cirebon, sebanyak 24,9% baduta mengalami stunting. Permasalahan stunting yang terjadi selama periode usia baduta adalah kurangnya asupan nutrisi yang dipengaruhi oleh pola asuh ibu dalam pemberian makan pada anaknya. Tujuan penelitian ini untuk mengetahui asupan gizi dan pola makan anak stunting usia 12-23 bulan di desa lokus Kabupaten Cirebon. Desain penelitian ini adalah adalah mixed method dengan strategi sequential explanatory. Penelitian kuantitatif untuk melihat asupan makan anak stunting sedang penelitian kualitatif digunakan untuk mengetahui pola makan anak stunting usia 12-23 bulan. Jumlah sampel kuantitatif 40 orang, dilakukan secara total sampling, sedang kualitatif sebanyak 10 orang dilakukan secara purposive sampling. Pengumpulan data kuantitatif dilakukan melalui pengukuran tinggi badan anak dan multiple 24 hour recall selama 3 hari. Pengumpulan data kualitatif dilakukan dengan wawancara mendalam. Analisis data kuantitatif dilakukan secara deskriptif, sedang analisis data kualitatif dilakukan melalui transkripsi, koding, kategorisasi, pembuatan tema. Hasil penelitian menunjukkan bahwa asupan gizi anak stunting usia 12-23 bulan di desa lokus Kabupaten Cirebon adalah tidak adekuat untuk energi, protein, vitamin A, vitamin C, kalsium, dan seng. Pola makan anak stunting usia 12-23 bulan di desa lokus Kabupaten Cirebon adalah menu yang tidak variatif, frekuensi pemberian makan yang tidak sesuai, jumlah yang kurang, jenis yang tidak beragam dan jadwal yang tidak teratur dari yang dianjurkan. Asupan gizi belum memenuhi kebutuhan anak, sedangkan pola makan belum sesuai dengan standar Kemenkes. Kata kunci: asupan gizi, pola makan, anak stunting, usia 12-23 bulan